Rate, Delay and Predictors of Hepatitis C Treatment in British Columbia - Alan Hoi Lun Yau; Terry Lee; Alnoor Ramji; Hin Hin Ko (Canadian Journal of Gastroenterology and Hepatology)
BACKGROUND: The current treatment rate for chronic hepatitis C virus (HCV) infection is suboptimal despite the availability of efficacious antiviral therapy.